1998
DOI: 10.1016/s1081-1206(10)62992-4
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae and Exacerbations of Asthma in Adults

Abstract: Our data suggest that C. pneumoniae infection may trigger acute exacerbations of adult asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 21 publications
3
41
0
2
Order By: Relevance
“…In one study of adults with asthma, infection with C. pneumoniae was responsible for 10% of all acute exacerbations [106], similar to rates reported in children aged 5-16 yrs experiencing an acute episode of wheezing [101]. The higher prevalence rates of C. pneumoniae among adults with asthma, as compared to age-matched controls, have also been linked to acute exacerbations [107].…”
Section: Exacerbationsmentioning
confidence: 66%
“…In one study of adults with asthma, infection with C. pneumoniae was responsible for 10% of all acute exacerbations [106], similar to rates reported in children aged 5-16 yrs experiencing an acute episode of wheezing [101]. The higher prevalence rates of C. pneumoniae among adults with asthma, as compared to age-matched controls, have also been linked to acute exacerbations [107].…”
Section: Exacerbationsmentioning
confidence: 66%
“…Most respiratory infections caused by C. pneumoniae are mild or asymptomatic. Many studies have suggested a possible association of C. pneumoniae infection and acute exacerbations of asthma and chronic obstructive pulmonary disease (14,15,19,26,30). Seroepidemiological studies showing antibody prevalence rates in a range of 50 to 70% suggest that C. pneumoniae is widely distributed and that nearly everybody is infected with the agent at some time (15,19,24).…”
Section: Discussionmentioning
confidence: 99%
“…24 Because the Solomon Islands are a region that is highly endemic for malaria, 25 respiratory diseases, and viral infections, 26 recurrent C. pneumonae infections might also occur there frequently. High prevalence rates of IgA have been observed in chronic pulmonary diseases, 27,28 such as in the acute exacerbation of bronchial asthma, [29][30][31] suggesting a relationship with persistent respiratory disease. Wang and Grayston 18 reported the prevalence of IgG determined by the MIF method to be 15% in the Solomon Islands in a small number of serum samples collected in 1966.…”
Section: Discussionmentioning
confidence: 99%